Nutraceutical properties, biological activities, and industrial applications of chickpea protein - Sidra Akram; Muhammad Faizan Afzal; Kainat Anwer; Laiba Farman; Muhammad Zubair; Safura Kousar; Touseef Iqbal; Waseem Khalid; Mohammed Ahmed Elawad; Alshebli Ahmed; Muhammad Zubair Khalid; Felix Kwashie Madilo (Cogent Food & Agriculture)
The demand for protein has increased over last few years. Plant-based proteins are appreciated to meet the increasing demand of proteins than animal protein with the growing population worldwide. Pulses are one of the good sources of protein. Chickpea is one of the oldest and most cultivated legume crops consumed as source of protein. Chickpeas can be classified into two types named as ‘kabuli’ and ‘desi’ on the basis of their physical parameters. They are recognized as a valuable dietary protein source due to their sufficient biological value, and protein bioavailability. Chickpeas contain a variety of bioactive compounds, including isoflavones and phenolic acid. Generally, chickpea and pulses serve as viable options for functional and nutritional proteins. Chickpea proteins are considered as the best alternative to animal proteins with high amino acid profile and cost effectiveness. They are significant in academic and food business domains. Chickpea protein isolates are commonly identified as having a minimum protein content of 90% on a dry weight basis. They offer excellent functional and therapeutic potential in mitigating various health ailments. Chickpea protein is also used in production of value-added products in various food industries including baking industries, meat industry, infant formula and nutraceutical industries. This review explores the production, nutritional composition, health perspectives and industrial applications of chickpea protein.